Tribhuvan Vishwovidhyalayako Anusandhan Niti Tatha Karyakram ak Adhyayan - Sharma, Nilam Kumar (Tribhuvan University Journal, 2010)
Not available.Key words: Research Policy; Tribhuvan University; Nepal Tribhuvan University Journal Vol. XIX, No. 2, 1996 Page:  135-143      Uploaded Date: 31 October, 2010